Development of Prototyping Regenerative Power Braking - Queck, Bun Lim; Sulaiman, Syabillah; Muhammad Asri Azizul, (Progress in Engineering Application and Technology, 2024)
Regenerative braking system is a promising energy recovery mechanism to achieve energy saving in mostly Electric and Hybrid Vehicle. This system enables the recovery of kinetic energy that is dissipated during vehicle braking maneuvers, which would otherwise be wasted as heat or lost energy. With the aims of maximizing energy recovery efficiency, optimal system design and integration play a crucial role. This research paper focus investing the amount of energy can be produced by a Dynamo Hub by conducting an actual experiment to analyse the amount of voltage can be generate with different parameters and also to analyze the effficiency of eletrical energy generate from braking. This experiment would be conducted on a Yamaha LC135 motorcycle with the regenerative braking system installed on the rear wheel that was supported by dynamo frame, the data collected were obtained with help of Arduino UNO that to capture the energy that produced. One experiment focus on how to increase 1% of charging within a fix route and the other one was generating a different output voltage with variable speeds. The outcome came with as approaching higher speed, the voltage and energy produced by the system also increase. However, if the braking time was short, a higher voltage alone may not necessarily mean more energy recovery as time play a crucial role in regenerative braking. Essentially, this system experience a significant energy lost of 99%, despite the loss, some energy still produced underscores the validility of the regenerative braking system concept. This study proposes the harnessing of waste energy in daily life activities, with the aim of transforming it into electrical energy to the greatest extent possible.